Exploring the Potential of Hesperidin in Preventing Hypertrophic Scars: Insights from a Rabbit Ear Model - Yang P; Zhong J; Zhao X; Ali K; Wu L; Bu Z (Dove Medical Press, 2023)
Ping Yang,1,* JianBo Zhong,1,* XingYun Zhao,1 Kamran Ali,1,2 Liming Wu,1 ZhangYu Bu1 1Department of Dermatology, Affiliated Hangzhou First People's Hospital, Zhejiang University School of Medicine, Hangzhou, Zhejiang, People's Republic of China; 2Department of Oncology, The Fourth Affiliated Hospital, International Institutes of Medicine, Zhejiang University School of Medicine, Yiwu, Zhejiang, People's Republic of China*These authors contributed equally to this workCorrespondence: Liming Wu, Department of Dermatology, Affiliated Hangzhou First People's Hospital, Zhejiang University School of Medicine, No. 261, Huansha Road, Hangzhou, People's Republic of China, Tel/Fax +86 13750837205, Email limingwu1973@163.comBackground: Hypertrophic scars, commonly occurring after trauma or surgery in critical areas like the head and joints, pose significant challenges to both physical and mental health due to their impact on skin function and aesthetics. While the complex pathogenesis involves fibroblast activation and collagen deposition, effective treatments are lacking, underscoring the importance of exploring pathogenesis and targeted therapies. Hesperidin, a bioactive compound in citrus fruits with diverse health benefits, including anti-fibrotic and anti-angiogenic effects, is the focus of this study with the aim of investigating its impact on hypertrophic scar formation, given its potential to promote blood flow and improve skin microcirculation.Objective: This study aimed to observe the inhibitory effect of topical hesperidin on hypertrophic scars in rabbits.Methods: A total of 8 healthy adult New Zealand white rabbits were used to establish a rabbit hypertrophic scarring animal model. Five wounds were created on each rabbit's two ears, with three wounds on the left ear (groups A, B, and C) and two wounds on the right ear (groups D and E). After six days of wound drying postoperatively, the wounds were locally treated with medication as followed: group A, 0.1% hesperidin; group B, 1% hesperidin; group C, 1% triamcinolone acetonide; group D, Vaseline; and group E, blank control without any medication. After 28 days, the scar tissue samples were collected for histological examination.Results: The results showed that the scar texture of groups B and C was softer and lighter in color, and the number of fibroblasts, capillaries, and inflammatory cells in the tissue was significantly less than those in the other three groups. The hypertrophic scar indices of groups B and C were significantly smaller than those of groups A, D, and E, and the difference was statistically significant (P < 0.05). There were no significant difference between groups B and C.Conclusion: Topical application of hesperidin demonstrated promising potential for reducing hypertrophic scar formation in rabbits.Plain Language Summary: Hypertrophic scars are a common problem that can occur after trauma or surgery, causing functional and aesthetic issues in areas such as the head, face, neck, and joints. The formation of these scars involves complex processes including fibroblast activation and collagen deposition. Effective treatments for hypertrophic scars are currently lacking, and understanding their pathogenesis and developing targeted therapies are important.Hesperidin (HDN), a compound found in plants like bitter orange and citrus peel, has various biological activities and has been found to have anti-fibrotic and anti-angiogenic effects in some studies. Traditional Chinese medicine believes that scars are caused by Qi stagnation and blood stasis, and that hesperidin has been shown to improve skin microcirculation, aligning with the principles of blood activation and stasis removal.This study aimed to observe the effects of hesperidin on hypertrophic scar formation using animal models. Eight rabbits were divided into different groups and treated with different formulations of hesperidin or other control substances. Scar tissue samples were collected and examined after 28 days.The results showed that hesperidin-treated scars had a softer texture and lighter color than the control scars. Histological analysis revealed reduced scar thickness, more organized collagen fibers; and fewer fibroblasts, capillaries, and inflammatory cells in the hesperidin-treated groups. The 1% hesperidin group showed comparable effects to the corticosteroid triamcinolone acetonide group.These findings suggest that hesperidin has anti-inflammatory, anti-fibroblast proliferation, and anti-angiogenic properties and effectively inhibits hypertrophic scar formation in rabbits. Further research is needed to determine its efficacy and safety in human, and to establish appropriate dosages for therapeutic use. Overall, hesperidin holds promise as a potential treatment for preventing and treating skin scars.Keywords: hesperidin, hypertrophic scar, rabbit ear